CD2 Regulates Pathogenesis of Asthma Induced by House Dust Mice Extract - Hashem, Tanwir; Kammala, Ananth K.; Thaxton, Kanedra; Griffin, Ryan M.; Mullany, Kellie; Panettieri, Reynold A.; Subramanian, Hariharan; Das, Rupali (Frontiers in Immunology, 2020)
Characteristic of allergic asthma, CD4+Th2 lymphocytes secrete Th2 cytokines, interleukin (IL)-4, IL-13, and IL-5 that mediate the inflammatory immune response. Surface expression of CD2 and its ligand, CD58, is increased on the monocytes and eosinophils of asthma patients, which correlate with elevated serum IgE levels, suggesting that CD2 may contribute to allergic airway inflammation. Using a murine model of asthma, we observed that house dust mice extract (HDME)-exposed Balb/c mice have increased airway hyperresponsiveness (AHR), lung inflammation, goblet cell hyperplasia, and elevated levels of Th2 cytokines in the lungs, as well as increased serum IgE levels as compared to the control mice. In contrast, with the exception of serum IgE levels, all the other parameters were significantly reduced in HDME-treated Cd2−⁄− mice. Interestingly, Il13 but not Il4 or Il5 gene expression in the lungs was dramatically decreased in HDME-exposed Cd2−⁄− mice. Of note, the gene expression of IL-13 downstream targets (Muc5b and Muc5ac) and high affinity IL-13Ra2 were upregulated in the lungs of HDME-exposed Balb/c mice but were significantly reduced in HDME-exposed Cd2−⁄− mice. Consistently, gene expression of microRNAs regulating mucin production, inflammation, airway smooth muscle cell proliferation and IL-13 transcripts were increased in the lungs of HDME-exposed Cd2−⁄− mice. Given the established role of IL-13 in promoting goblet cell hyperplasia, lung inflammation and AHR in allergic asthma, our studies reveal a unique role for CD2 in the regulation of Th2-associated allergic asthma.